Imagem & tecnologia: webmuseu de arte - Lima, Fábio Rogério Batista [UNESP] (2012)
With the presence of Cyberspace, web museums emerged, which are characterized as informational environments with exhibitions of artworks presented virtually, affecting the use of the image. Using an access device to the Internet, anyone can visit the works of established artists without leaving the place they are, which is a characteristic of ubiquity (being present in several places at the same time) offered by information and communication technologies (ICT), which was possible only with the geographic displacement to in-person visits. The formal and the artworks contents transformation in its transposition into digital environments is a consequence of the passage of a semiotic structure to another, which causes changes in the aesthetic quality of the work produced in different support from the one which is being presented in the digital environment for the construction of imagery information (size, color, shape, etc.) in digital museums. The digitalization and transposition of artworks to digital catalogs (digital version of the traditional catalogs) and /or web museums, create simulacra of the original works and its organic and material form transforms into computer language of bits and bites. In this context, were analyzed the impacts that information and communication technologies (ICT) cause the aesthetics of images available in these environments. Using the bibliographic descriptive method, the objective was to determine the characteristics of printed artworks catalogs, museums and web museums websites to demonstrate their ... (Complete abstract click electronic access below)